Salvia officinalis L. Essential Oil: Characterization, Antioxidant Properties, and the Effects of Aromatherapy in Adult Patients - Maria-Daniela Mot; Simona Gavrilaș; Andreea I. Lupitu; Cristian Moisa; Dorina Chambre; Delia Mirela Tit; Mihaela Alexandra Bogdan; Adina-Maria Bodescu; Lucian Copolovici; Dana Maria Copolovici; Simona Gabriela Bungau (MDPI AG, 2022)
The purpose of this study is to reveal the chemical and biochemical characteristics and the potential aromatherapy applications of the essential oil (EO) of Salvia officinalis (common sage) within a hospital environment. The chemical composition was determined by gas chromatography with mass spectrometry and ATR-FTIR spectroscopy. Three types of sage EOs were included in this study: two commercial oils and one oil obtained by in-house hydrodistillation. Based on the findings, these EOs were included in different chemotypes. The first two samples were similar to the most common chemotype (α-thujone > camphor > 1,8-cineole > β-thujone), while the in-house sage EO revealed a high content of 1,8-cineole, borneol, α-thujone, similar to the Dalmatian type. The latter sample was selected to be evaluated for its antioxidant and medical effects, as borneol, a bicyclic monoterpene, is known as a substance with anesthetic and analgesic effects in traditional Asian medicine. The study suggests that the antioxidant capacity of the sage EO is modest (33.61% and 84.50% inhibition was determined by DPPH and ABTS assays, respectively), but also that the inhalation of sage EO with high borneol content by hospitalized patients could improve these patients' satisfaction.